Diabetes Related Knowledge, Attitude and Practice among Diabetic Patients Attending at Chittagong Medical College Hospital - Azim, Mohammed Noorul; Deb, Ajoy; Khanam, Zubaida; Akter, Shamim; Roy, Binimoy Baran; Farahnaz, Sara; Chowdhury, Sanjida (IAHS Medical Journal, 2024)
Background: Increased awareness among large population groups is a major determinant for the prevention of diabetes and its complications. Knowledge and attitude are the principal markers of awareness that need to be studied in various population groups in specific racial and cultural contexts. Therefore, good Knowledge, Attitude and Practices (KAP) regarding diabetes are necessary in promoting care. This study aimed to explore Knowledge, Attitude and Practices (KAP)-regarding Diabetes Mellitus (DM) among diabetic patients attending in Chittagong Medical College Hospital. Materials and methods: This cross-sectional study was conducted from January 2022 to December 2022 among 289 diabetic patients from the outpatient department of Chittagong Medical College Hospital, Chattogram. KAP were assessed by a pre-structured, interviewer-administered questionnaire and categorized using predefined scores of poor (<< 30%), average (30-70%) and good (70%). Chi-square test was done to examine the association between diabetes related KAP and other covariates. Results: Out of 289 participants 167(57.8%) of the participants had good knowledge, 208 (72%) had positive attitude and 173 (60%) had good practice related to DM. Poor knowledge was significantly associated with female gender (p=0.010), being housewife (p=0.023) and low socioeconomic status (p <0.001). Conclusion: Present study identified some gap in KAP related to DM and some factors related to poor knowledge, negative attitude and poor practices among the diabetic patients, which highlighted the need of more comprehensive approach for DM related management in the study hospital. IAHS Medical Journal Vol 6(2), December 2023; 44-47